1994
DOI: 10.1172/jci117477
|View full text |Cite
|
Sign up to set email alerts
|

Dietary obesity linked to genetic loci on chromosomes 9 and 15 in a polygenic mouse model.

Abstract: Loci linked to sensitivity to dietary obesity were identified by Quantitative Trait Locus (QTL) analysis of two mapping populations derived from a cross between AKR/J and SWR/J mice. AKR/J mice are sensitive to dietary obesity when fed a high fat diet while SWR/J mice are resistant. Intercrosses between these strains segregate the phenotype of sensitivity to dietary obesity. Using an F2 mapping population of 931 male mice we found significant linkage with a QTL on chromosome 9 (Likelihood of the Odds [LOD] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(64 citation statements)
references
References 33 publications
(25 reference statements)
4
58
0
2
Order By: Relevance
“…Comparative genome analysis data showed that Ins/gk1 and Chol/gk1 are conserved with a region of mouse chromosome 9, previously characterised for the obesity QTL Dob2 and Mob8 [23,24,25], and human chromosomes 11q22.3-24.3, 15q21.2-25.1 and 6p21.1-q14.1. The region of human 15q, which contains the locus LIPC and is associated with variations in HDL-C concentrations in Mexican Americans [26], seems to be homologous to Chol/gk1.…”
Section: Discussionmentioning
confidence: 87%
“…Comparative genome analysis data showed that Ins/gk1 and Chol/gk1 are conserved with a region of mouse chromosome 9, previously characterised for the obesity QTL Dob2 and Mob8 [23,24,25], and human chromosomes 11q22.3-24.3, 15q21.2-25.1 and 6p21.1-q14.1. The region of human 15q, which contains the locus LIPC and is associated with variations in HDL-C concentrations in Mexican Americans [26], seems to be homologous to Chol/gk1.…”
Section: Discussionmentioning
confidence: 87%
“…4 In fact, for at least 13 QTL, evidence for linkage of body weight and body fat percentage was found within the same study, including Adip2, Adip3, Adip4a, Adip8, Bfq1, Bwnd5wk6, Do2, Do3, Do7, Kcal3, Nob1, Nzoq2, and Obq5. [51][52][53][54][55][56][57][58][59][60] It appears that most of these QTL involved cross-breeding experiments with parental mouse strains that show a relatively high (AKR, NZO, KK) and low (CAST, SM, SJL) body weight and (Figures 2 and 3). The contribution of QTL to certain consensus regions apparently correlates with the parental mouse strain.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is not unprecedented. In studies of genetic modifiers of the L e p r f a mutation, Chung et al (29) found that the susceptibility alleles to L e p r f a -associated diabetes are not always derived from the susceptible strain, a phenomenon known as "transgression" that has also been seen in studies of QTL controlling body fat and diet (46,47). A possible explanation is that these alleles are silenced by more dominant alleles in the context of the resistant strain but are active in the context of the susceptible strain.…”
Section: Ta B L E 2 Distribution Analysis (mentioning
confidence: 99%